Influence of the Type of Basal Insulin and Other Variables on Clinical Outcomes in Children with Newly Diagnosed Type 1 Diabetes. (6th February 2014) - Garrison, Ruth M.; Johnson, Jeremy L.; Condren, Michelle E.; Farmer, Kevin C.; Jelley, David H.
Abstract : Background . Basal insulin detemir and glargine each have characteristics that may make them a superior choice in children and adolescents with type 1 diabetes, but there is a paucity of data on glycemic results in this population. Objective . Examination of variables associated with achievement of HbA1c goal in children and adolescents with newly diagnosed type 1 diabetes. Methods . The primary outcome, factors associated with achievement of HbA1c goal, was examined in a retrospective chart review. Variables, including type of basal insulin, were collected during the first year of diagnosis of patients in a pediatric diabetes clinic. Secondary outcomes included change in HbA1c, severe hypoglycemic events, and episodes of DKA. Results . 94 patients were included in the study. HbA1c at diagnosis was found to be a significant predictor of achievement of goal at 3 months (P = 0.002 ) and of change in HbA1c at 3 and 12 months (P < 0.001 for each). Severe hypoglycemia and episodes of DKA were uncommon. Conclusions. Choice of basal insulin was not found to be a predictor of achieving HbA1c goal or of change in HbA1c over the course of the first year of diagnosis with type 1 diabetes.